2016
DOI: 10.1542/peds.2015-4441
|View full text |Cite
|
Sign up to set email alerts
|

Improving Safe Sleep Practices for Hospitalized Infants

Abstract: BACKGROUND AND OBJECTIVES: Adherence to the American Academy of Pediatrics safe sleep practice (SSP) recommendations among hospitalized infants is unknown, but is assumed to be low. This quality improvement study aimed to increase adherence to SSPs for infants admitted to a children’s hospital general care unit between October 2013 and December 2014. METHODS: After development of a hospital policy and redesign of room setup p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 23 publications
4
31
0
Order By: Relevance
“…The Back to Sleep campaign was launched in 1994 in an effort to reduce the rates of sudden infant death syndrome (SIDS) in the United States. The initial campaign, encouraging parents to put their infants to sleep in a non-prone position after research demonstrated an association between the prone sleep position and an increased risk of SIDS, reached a wide audience and was incredibly successful (AAP Task Force, 2016;Moon, 2016;Shadman, Walk, Smith, & Coller, 2016). Between 1994 and2001, rates of SIDS declined dramatically (Moon, 2016;Shadman et al, 2016).…”
Section: Problem Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Back to Sleep campaign was launched in 1994 in an effort to reduce the rates of sudden infant death syndrome (SIDS) in the United States. The initial campaign, encouraging parents to put their infants to sleep in a non-prone position after research demonstrated an association between the prone sleep position and an increased risk of SIDS, reached a wide audience and was incredibly successful (AAP Task Force, 2016;Moon, 2016;Shadman, Walk, Smith, & Coller, 2016). Between 1994 and2001, rates of SIDS declined dramatically (Moon, 2016;Shadman et al, 2016).…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The initial campaign, encouraging parents to put their infants to sleep in a non-prone position after research demonstrated an association between the prone sleep position and an increased risk of SIDS, reached a wide audience and was incredibly successful (AAP Task Force, 2016;Moon, 2016;Shadman, Walk, Smith, & Coller, 2016). Between 1994 and2001, rates of SIDS declined dramatically (Moon, 2016;Shadman et al, 2016). Ongoing research over the last thirty years has expanded our understanding of SIDS risk factors and, in response, the American Academy of Pediatrics (AAP) continually updates the recommended safe sleep practices (SSP) for infants (Moon, 2016).…”
Section: Problem Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent publications, multiple authors have described QI interventions in the nursery that demonstrated improvements in nurse' s knowledge and practice around safe sleep practices. [4][5][6] Although improvements were demonstrated in in-hospital process measures, Shadman et al 5 found no change in parent home practices after discharge. In other studies, it has been demonstrated that health care providers are a significant source of education for safe sleep and that information given at the time of delivery translates to improved compliance with safe sleep recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been demonstrated that hospital safe sleep education using quality improvement (QI) methodology may improve the modeling of safe sleep practices in hospitals [4][5][6] but fails to impact postdischarge outcomes. 5 It is not surprising that a generic single-dose educational strategy such as discharge counseling would not impact outcomes given that authors of previous health and safety-related behavior change research demonstrate little impact on postdischarge practices of adults with diverse backgrounds, lifestyles, and parenting experience. 7 Additionally, there is evidence that parents recall little of the anticipatory guidance delivered in the newborn nursery.…”
mentioning
confidence: 99%